Impact of NPSB fertilizer on yield of orange-fleshed sweet potato (Ipomoea batatas (L.) Lam.) varieties in Southern Ethiopia's agro-ecological zones - Amelewerk Gizachew; Sabura Shara; Asfaw Kifle (Heliyon)
Root and tuber crops, particularly sweet potatoes, are vital to global food security, yet their potential for enhancing household nutrition and income remains largely untapped. Orange-fleshed sweet potato (OFSP) varieties are rich in pro-vitamin A, crucial for health. Despite their significance in Ethiopia, yields are often low due to inadequate location-specific fertilizer recommendations and limited access to high-yielding varieties. This study aimed to determine the optimal blended NPSB fertilizer rates and high-yielding OFSP varieties in the contrasting environments of Wolaita and Gamo zones, where these crops are staples. We evaluated three OFSP varieties (Alamura, Dilla, and Kabode) and four NPSB rates (0, 79.5, 159, and 238.5 kg ha−1 in a 3x4 factorial experiment using a randomized complete block design (RCBD) with three replications during the 2022 cropping season. Data on root yield and yield components were analyzed using the GLM procedure in SAS 9.2. Partial budget analysis and agronomic efficiency were also computed. Results showed that marketable root yield and root dry matter were significantly affected by the interaction of site, fertilizer rates, and OFSP varieties. The highest marketable root yield (49.84 t ha−1 and net benefit (342,856.6 ETB ha−1) were achieved with the Kabode variety at 238.5 kg NPSB in Arba Minch, while the same variety yielded the highest net benefit from 159 kg NPSB in Areka. The highest agronomic efficiency was recorded at 159 kg NPSB and 79 kg NPSB in Arba Minch (174.71) and Areka (288.67), respectively, indicating a negative relationship between net benefit, agronomic efficiency, and increasing NPSB rates. In conclusion, cultivating the Kabode variety with 159 kg ha−1 NPSB in Arba Minch and 79.5 kg ha−1 NPSB in Areka is recommended for enhancing sweet potato productivity, thereby improving food security and nutritional benefits for smallholder farmers in the region.